2012
DOI: 10.1103/physrevlett.109.152303
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Pseudorapidity and Centrality Dependence of the Transverse Energy Density in Pb-Pb Collisions atsNN=2.76TeV

Abstract: The transverse energy (E T ) in Pb-Pb collisions at 2.76 TeV nucleon-nucleon center-of-mass energy ( ffiffiffiffiffiffiffiffi s NN p ) has been measured over a broad range of pseudorapidity () and collision centrality by using the CMS detector at the LHC. The transverse energy density per unit pseudorapidity (dE T =d) increases faster with collision energy than the charged particle multiplicity. This implies that the mean energy per particle is increasing with collision energy. At all pseudorapidities, the tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 35 publications
3
73
0
Order By: Relevance
“…± 0.50(sys.) GeV, two standard deviations below the value observed by CMS [30]. All methods resulted in a lower E T than that reported by CMS, although the systematic errors on the measurements are significantly correlated.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…± 0.50(sys.) GeV, two standard deviations below the value observed by CMS [30]. All methods resulted in a lower E T than that reported by CMS, although the systematic errors on the measurements are significantly correlated.…”
Section: Resultsmentioning
confidence: 49%
“…All methods resulted in a lower E T than that reported by CMS, although the systematic errors on the measurements are significantly correlated. One possible explanation of the differences is that the corrections for the CMS calorimetry measurement are determined by Monte Carlo [30], while the corrections for the ALICE measurement are mainly data driven. PHENIX [28] reported that while dE T /dη scaled by N part has a pronounced centrality dependence, as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe very good agreement up to Let us see how lattice QCD predictions compare with heavy ion experiments at RHIC and the LHC. Phenomenological estimates on the energy density reached at the initial stage of the collision range from e ≈ 5.6 GeV/fm 3 for Au-Au collisions at RHIC with √ s N N = 200 GeV [131], to e ≈ 15 GeV/fm 3 for Pb-Pb collisions at the LHC with √ s N N = 2.76 TeV [132]. Looking at the right panel of Fig.…”
Section: Thermodynamics With Physical Quark Massesmentioning
confidence: 99%
“…Using minimum bias PbPb collision events collected by CMS at nominal magnetic field at center-of-mass energy of 2.76 TeV per nucleon it is possible to extend the absolute measurement of the energy flow, dE/dη, into the region close to the beam rapidity (y beam = 7.99) [4,5]. The CASTOR energy scale is set via a cross-calibration procedure according to energy pseudorapidity density measured in the HF calorimeter using an independent data set of minimum bias pp collision events at 7 TeV center-of-mass energy.…”
Section: Measurement Of De/dη In Pbpb Collisionsmentioning
confidence: 99%